A Feeder Protection Scheme for DC Micro-Energy System - Song, Haitao; Yang, Li; Chen, Shaoyu; Huang, Wentao; Tai, Nengling (Frontiers in Energy Research, 2021)
DC micro-energy system is an effective pattern to integrate high-penetration distribution generators. It has flexible operation modes and complicated fault characteristics, which requires protection with higher selectivity and sensitivity. This paper proposes a DC feeder protection method using the transient high-frequency currents. The fault direction and fault feeder are identified by comparing the amplitude of high-frequency currents of all ends. The amplitude ratio coefficient of DC voltages is introduced to detect the fault pole. The transient high-frequency components will not be affected by the communication delay and fault impedance. The protection scheme realizes the fast detection and clearance of different faults on feeders before the failure of the inverter-interfaced generators and loads, which ensure the reliable and safe operation of the non-fault zone. The model of a DC micro-energy system is established in MATLAB/Simulink and the efficiency of this method is verified by detailed simulations.